Primers designed for the detection of grapevine pathogens spreading with propagating material by quantitative real-time PCR - Czotter, N.; Manduláné Farkas, E.; Lózsa, R.; Ember, I.; Szûcsné Varga, G.; Várallyay, É.; Szegedi, E. (International Journal of Horticultural Science, 2015)
Several grapevine pathogens are disseminated by propagating material as systemic, but latent infections. Their detection and identification have a basic importance in the production and handling of propagating stocks. Thus several sensitive and reliable diagnostic protocols mostly based on molecular techniques have been developed. Of these methods quantitative real-time PCR (q-PCR) has recently got an emerging importance. Here we collected primer data for the detection and identification of grapevine pathogens which are important in the production of propagating stocks by q-PCR. Additional novel techniques that use DNA amplification, hybridization and sequencing are also briefly reviewed.